1993
DOI: 10.1021/bi00082a011
|View full text |Cite
|
Sign up to set email alerts
|

Affinity purification and binding analysis of the hemolymph juvenile hormone binding protein from Manduca sexta

Abstract: A high-affinity juvenile hormone binding protein was purified from the hemolymph of the tobacco hornworm, Manduca sexta, employing ammonium sulfate precipitation and affinity and sizeseparation chromatography. The naturally occurring enantiomer of juvenile hormone III (107?) was converted to juvenile hormone III acid and then covalently attached to aminohexyl-Sepharose 4B. Hemolymph from early fifth stadium (60 h postecdysis) larvae was used as the source of hJHBP. The yield of hJHBP was approximately 25% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…As a positive control, the same amount of tritiated JH was incubated with 250l hemolymph from Manduca sexta fourth instar larvae, which contains a 34-36kDa JH binding protein, JHBP (Goodman et al, 1978;Park et al, 1993;Orth et al, 2003). After incubation, samples of BSA and M. sexta hemolymph were separated in duplicate on 10% native gels at 180V.…”
Section: Jh Assays Juvenile Hormone Binding Assaymentioning
confidence: 99%
“…As a positive control, the same amount of tritiated JH was incubated with 250l hemolymph from Manduca sexta fourth instar larvae, which contains a 34-36kDa JH binding protein, JHBP (Goodman et al, 1978;Park et al, 1993;Orth et al, 2003). After incubation, samples of BSA and M. sexta hemolymph were separated in duplicate on 10% native gels at 180V.…”
Section: Jh Assays Juvenile Hormone Binding Assaymentioning
confidence: 99%
“…The molecular identification of the to gene has revealed that it shares structural homology with JHBPs (Sarov-Blat et al, 2000). JH, synthesized in the corpus allatum, circulates in haemolymph bound to JHBPs, which serve as carriers for this hydrophobic hormone (Park et al, 1993). Further investigation needs to be done to demonstrate that TO could be a carrier for JH.…”
Section: Why Do To 1 Flies Die Faster Than Wt During Starvation?mentioning
confidence: 99%
“…We also assayed JH binding by the DEAE-cellulose filter binding assay (Peterson, 1985) and equilibrium dialysis (Park et al, 1993).…”
Section: Juvenile Hormone Binding Assaysmentioning
confidence: 99%